Extractive Metallurgy Division - Effect of Chloride on the Deposition of Copper, in the Presence of Arsenic, Antimony, and Bismuth - V. Hospadaruk; C. A. Winkler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1954)
PREVIOUS papers from this laboratory have discussed the effect of chloride ion on the cathode polarization during electrodeposition of copper from copper sulphate-sulphuric acid electrolytes, in the presence and absence of gelatin. The steady state polarization'" was found to decrease sharply and pass through a minimum with increasing chloride ion concentration in the presence of gelatin. The minimum shifted to higher chloride ion concentrations and to higher polarization values with increase in current density or gelatin concentration, while an increase of temperature shifted the minimum toward lower halide concentrations and lower polarizations. Since these observations were made in acid-copper sulphate electrolytes that contained no other addend than gelatin, there was obviously the possibility that they were not applicable to deposition of copper from commercial electrolytes that contain a variety of other substances in relatively small amounts. In particular, it was of interest to determine whether the presence of arsenic, antimony, or bismuth in the electrolyte would materially alter the behavior. Experiments have now been made under a variety of conditions with systems containing these cations, and the results are summarized in the present paper. Experimental Polarization measurements were made at 24.5oC in a Haring cell in the manner described previously.' Electrolytes were made with doubly-distilled water, and contained 125 g per liter of copper sulphate and 100 g per liter sulphuric acid, both of reagent grade Eimer and Amend gelatin from a single stock was used throughout. Chloride ion was introduced as reagent grade sodium chloride, and arsenic, antimony, and bismuth by dissolving the chemically pure metal in hot concentrated sulphuric acid and adding appropriate amounts of the solutions to the electrolyte. Each cathode, of 1/16-in. thick rolled copper, was first etched in 40 pct nitric acid and washed thoroughly with distilled water. The surface was then brought to a standard condition4~9 by electrodeposition from an acid-copper sulphate electrolyte containing no gelatin, at a current density of 3 amp per sq dm for 30 min, followed by deposition at a current density of 2 amp per sq dm for l hr. As in previous studies, the cathode polarization eventually attained a steady-state value (15 to 75 min) such that further change in polarization did not exceed 0.2 mv per min. The polarization values recorded are those for the steady states. "Excess weights" were determined with arsenic and antimony present in the electrolyte, as the difference between the weights of the deposits obtained in the presence of these cations and those obtained in their absence, with the two cells connected in series. When gelatin was present along with the arsenic or antimony, it was also added to the electrolyte in the cell in series. Results and Discussion The results of the study are summarized in Figs. 1 to 6. From Fig. 1, top, it is evident that the presence of arsenic or antimony alone results in an increase of polarization, while bismuth alone causes a decrease. The presence of gelatin (25 mg per liter) rather drastically modifies all three cation effects, as indicated in the lower panels of the same figure. The addition of chloride ion, when no gelatin is present, causes comparable decreases in polarization in the presence of antimony and bismuth, but a relatively larger decrease when the electrolyte contains arsenic. It is interesting to note that the decrease in polarization brought about by addition of chloride when both arsenic and antimony are present parallels the behavior with arsenic alone, while the polarization in the electrolyte containing the cation mixture, without chloride added, corresponds to that for an electrolyte containing only the antimony cation. Similarly, the polarization at zero concentration of chloride in electrolyte containing arsenic and bismuth is that corresponding to an electrolyte containing arsenic alone. From Figs. 3a, 4a and 4b, it is clear that, in the presence of gelatin at a level of 25 mg per liter, the effect of chloride in the presence of arsenic and antimony, or a mixture of the two, becomes quite analogous to that observed in the absence of added cations. When both bismuth and gelatin are present (Fig. 5), the decrease in polarization with increased chloride concentration is virtually absent. This is perhaps a reflection of the large decrease in polarization brought about by the bismuth itself in the presence of gelatin. The shifts of the minimum in the polarization-chloride concentration curves brought about by changes of temperature (Fig. 3b), gelatin concentration (Figs. 3c and 4c) and current density (Fig. 3d) when the metal cations were present are all similar to the corresponding shifts observed in their absence." The approximately linear "excess weightv-anti-mony concentration relation recorded in Fig. 6 would seem to indicate that antimony is codeposited with copper to a considerable extent. On the other hand, only very limited amounts of arsenic appear to be adsorbed or codeposited.